PERAN MEDIASI KEPUASAN KERJA ATAS PENGARUH PROMOSI JABATAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (Studi pada Badan Kepegawaian Daerah Kota Pasuruan) - Nur Faridah; Muryati; T. Kuncoro (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The purpose of this research is to obtain empirical evidence about the ability to promote positions and organizational culture in encouraging increased employee performance, either directly or through the mediation of job satisfaction. This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 35 employees of the Pasuruan City Regional Civil Service Agency. Empirical findings show that promotion can encourage increased employee performance and job satisfaction. However, organizational culture is not able to encourage an increase in employee performance, but is able to encourage an increase in job satisfaction. The role of mediating job satisfaction is quite strong, because even though organizational culture is not directly able to influence employee performance, but if it is mediated through job satisfaction it turns out that organizational culture is able to encourage increased employee performance at the Pasuruan City Regional Civil Service Agency. These results indicate that job satisfaction has a strong mediating role.